2001
DOI: 10.1177/172460080101600109
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Significance of the Combined Expression of Matrix Metalloproteinase-9, Urokinase Type Plasminogen Activator and its Receptor in Breast Cancer as Measured by Northern Blot Analysis

Abstract: Using Northern blot analysis we have measured the co-expression of the matrix metalloprotease MMP-9, plasminogen activator urokinase type (uPA) and its receptor (uPAR) mRNAs in 81 biopsies of breast carcinomas with the objective of analyzing the impact of these factors on the overall survival probability of the patients (median follow-up time: 4 years). Individual mRNA levels of either uPA or uPAR showed parallel variations with MMP-9 mRNA, suggesting a coordinate transcription of these markers. When median va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
12
0
1

Year Published

2002
2002
2009
2009

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 28 publications
6
12
0
1
Order By: Relevance
“…For example, NF-B may regulate the production of prostaglandins via the proinflammatory gene cyclooxygenase-2 (COX2), which has been shown to be overexpressed in a variety of cancers including colorectal cancer and mesothelioma. [109][110][111] Similar studies have been found for many other pro-inflammatory genes regulated by NF-B including tumor necrosis factor 112 (TNF), interleukin-1 113 (IL-1), inducible NO-synthase 114 (iNOS), matrix metalloproteinase 115 (MMP-9), urokinase-type plasminogen activator 116 (uPA), and many other chemokines. [117][118][119] …”
Section: Nf-b and Tumor Promotionmentioning
confidence: 70%
“…For example, NF-B may regulate the production of prostaglandins via the proinflammatory gene cyclooxygenase-2 (COX2), which has been shown to be overexpressed in a variety of cancers including colorectal cancer and mesothelioma. [109][110][111] Similar studies have been found for many other pro-inflammatory genes regulated by NF-B including tumor necrosis factor 112 (TNF), interleukin-1 113 (IL-1), inducible NO-synthase 114 (iNOS), matrix metalloproteinase 115 (MMP-9), urokinase-type plasminogen activator 116 (uPA), and many other chemokines. [117][118][119] …”
Section: Nf-b and Tumor Promotionmentioning
confidence: 70%
“…UPAR activation ultimately leads to the degradation of the extracellular matrix, which seems to be necessary for functions as diverse as the local invasion and metastasis of tumor cells and for nerve growth factor-induced PC12 cell neurite outgrowth (19)(20)(21). Pacheco et al (22), using Northern blot analysis, measured the coexpression of the matrix metalloprotease MMP-9, UPA, and UPAR mRNAs in biopsy samples from patients with breast cancer and found that increased UPAR mRNA levels were associated with poor prognosis. In addition, it has been reported that sUPAR is a useful prognostic marker for patients with ovarian, breast, prostate, and colon cancer (23)(24)(25)(26)(27), although sUPAR has no known physiological function.…”
Section: Discussionmentioning
confidence: 99%
“…Ets-2 is involved in protein kinase A-stimulated hCG␤-5 expression (25 ) and is also involved in urokinase-type plasminogen activator and matrix metalloprotease-9 gene expression (26 ). Urokinase-type plasminogen activator and matrix metalloprotease-9 are matrix-degrading enzymes with prognostic value in breast cancer (27,28 ).…”
Section: Discussionmentioning
confidence: 99%